Implementasi Sistem Informasi Pelayanan Publik Terintegrasi (SI-PUTRI) (Kabupaten Ogan Komering Ilir, Provinsi Sumatera Selatan) - Wijaya, Fitra Andhika (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to analyze the implementation of the integrated public service information system (SI-PUTRI) which measures the level of the Community Satisfaction Index (IKM). The transition from manual assessment to digitalization makes it faster, easier, more transparent and integrated. With the SI-PUTRI innovation, the public can assess the public services of the Ogan Komering Ilir Regency government for the services provided to the community. SI-PUTRI makes it easier for the public to assess the level of satisfaction digitally so that the assessment is recorded in an integrated document so that it can make it easier for the government to evaluate the public services provided. The indicators of problems in implementing SI-PUTRI are factors that influence the relationship between SI-PUTRI and improving service performance. The second is factors that influence the success of SI-PUTRI implementation, such as the characteristics of implementing agents, work environment, social and political conditions and suitability. performance.